Systematic Review of Cesarean Scar Assessment in the Nonpregnant State: Imaging Techniques and Uterine Scar Defect - Roberge, Stéphanie; Boutin, Amélie; Chaillet, Nils; Moore, Lynne; Jastrow, Nicole; Demers, Suzanne; Bujold, Emmanuel (American Journal of Perinatology, 2012)
Objective To review the ability of imaging techniques to predict incomplete healing of uterine cesarean scars before the next pregnancy. Study Design A systematic literature review searched for studies on women who underwent previous low-transverse cesarean, evaluated by hysterography, sonohysterography (SHG), or transvaginal ultrasound (TVU). The median prevalence of scar defects was computed with 95% confidence intervals (95% CIs). Odds ratio (OR, 95% CI) identified risk factors of incomplete healing.Results The analysis included 21 studies. The proportions of suspected scar defects detected by hysterography, SGH, and TVU were 58% (33 to 70), 59% (58 to 85), and 37% (20 to 65), respectively. Two studies found that women with a large uterine scar defect had a higher risk of uterine rupture or uterine scar dehiscence than those with no scar defect or small scar defect (OR: 26.05 [2.36 to 287.61], p <0.001). The only reported risk factor for scar defect was the occurrence of more than one previous cesarean (OR: 2.24 [1.13, 4.45], p = 0.02).Conclusion Hysterography, SGH, and TVU can detect uterine scar defects in ~50% of women with previous cesarean.
Keywords: scar defects; cesarean; imaging techniques; ultrasound